2020
DOI: 10.1016/j.tranon.2020.100863
|View full text |Cite
|
Sign up to set email alerts
|

Age-related copy number variations and expression levels of F-box protein FBXL20 predict ovarian cancer prognosis

Abstract: About 70% of ovarian cancer (OvCa) cases are diagnosed at advanced stages (stage III/IV) with only 20–40% of them survive over 5 years after diagnosis. A reliably screening marker could enable a paradigm shift in OvCa early diagnosis and risk stratification. Age is one of the most significant risk factors for OvCa. Older women have much higher rates of OvCa diagnosis and poorer clinical outcomes. In this article, we studied the correlation between aging and genetic alterations in The Cancer Genome Atlas Ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…FBXL10 has been reported to act as a crucial tumor accelerator in gastric cancer [26], colon cancer [27], and breast cancer [28]. Additionally, studies have indicated that upregulation of the FBXL20 protein level is associated with malignant histological features of OC and that the depletion of FBXL20 activity may improve OC clinical outcomes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…FBXL10 has been reported to act as a crucial tumor accelerator in gastric cancer [26], colon cancer [27], and breast cancer [28]. Additionally, studies have indicated that upregulation of the FBXL20 protein level is associated with malignant histological features of OC and that the depletion of FBXL20 activity may improve OC clinical outcomes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating TMPRSS2-ERG and their alternative partners revealed six (out of 29) African-derived fusions with novel PCa partners to ETV4, ERG and TMPRSS2 , including FBXO7 , LINC01525, GTF3C2 and NTNG1. Classified as a potential tumour suppressor gene, disruption of FBXO47 has been reported in breast, ovarian and renal cancers [ 58 , 59 ], while to the best of our knowledge this is the first report of LINCO1525 disruption in any cancer. GTF3C2 is one member of the general transcription factor III family, which has been reported as a prognostic factor in liver cancer [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in concordance with previously published results indicating that CN variation is a common mechanism whereby cancer cells alter gene expression, resulting in immune evasion and higher levels of proliferation. [ 20,21 ]…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in concordance with previously published results indicating that CN variation is a common mechanism whereby cancer cells alter gene expression, resulting in immune evasion and higher levels of proliferation. [20,21] Observing these molecular changes and their correlations with reduced DFS, we sought to identify a specific AA sequence within MAGEB4 and TDRD1 responsible for the observed inverse relationship for the electrostatic CSs and DFS. However, fragmenting of TDRD1 revealed the opposing paradigm: high hydro CS for CDR3-TDRD1 Fragment 17 was associated with better DFS, replicated with two sources of CDR3s, the TCGA-OV WXS files and RNAseq files.…”
Section: Discussionmentioning
confidence: 99%